Republication of "Evidence-Based Practices in Special Education: Some Practical Considerations". (May 2015) - Cook, Bryan G.; Tankersley, Melody; Cook, Lysandra; Landrum, Timothy J.
A major tenet of both the Individuals with Disabilities Education Act and the No Child Left Behind Act is the identification and use of evidence-based practices, or those instructional techniques shown by research as most likely to improve student outcomes meaningfully. However, much confusion exists regarding the meaning and potential applications of evidence-based practices in special education. Evidence-based practices are traditionally supported by the findings of multiple, high-quality, experimental research studies. Rather than changing the nature of teaching or limiting teachers to following prescribed methods, prioritizing evidence-based practices will allow teachers to maximize the impact of their instructional efforts.